PENGARUH PEMBELAJARAN BISNIS ONLINE TERHADAP INTENSI BERBISNIS DIGITAL DENGAN KOMPETENSI DIGITAL SEBAGAI VARIABEL INTERVENING - Sidupa, Alfina Marsha Kristianty; Saino, Saino (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This research aims to determine the influence of online business learning on digital business intentions mediated by digital competence in BDP graduates in vocational schools in the Jombang area, including through SMKN Mojoagung, SMKN 1 Jombang, and SMK PGRI 1 Jombang. The type of research used is descriptive quantitative, where the sample in the research consists of 200 respondents. The data collection technique uses a research instrument in the form of an online questionnaire using Google form, which is distributed to BDP graduates class of 2023 from SMKN Mojoagung, SMKN 1 Jombang, and SMK PGRI 1 Jombang. The online business learning variable (X) has a significant effect on digital business intentions (Y). The online business learning variable (X) has a significant effect on digital competence (Z). The digital competency variable (Z) has no significant effect on digital business intentions (Y). The online business learning variable (X) mediated by digital competence (Z) has no significant effect on digital business intentions (Y).